Structurally Constrained Insulin Analogs by Directed Stepwise Crosslinking - Zhang, Fa; Mayer, John P.; Gelfanov, Vasily; Liu, Fa; DiMarchi, Richard D. (Protein and Peptide Letters, 2018)
Background: Research has been directed at the optimization of insulin for medicinal purposes. An insulin analog that could be reversibly activated might provide more precise pharmacokinetic control and broaden the inherent therapeutic index of the hormone. The prospect of using intramolecular structural constraint to reversibly inactive insulin might constitute the first step to achieving such an optimized analog. Chemically crosslinked insulin analogs have been reported where two amines are covalently linked by reaction with symmetrical bifunctional active esters. There is little selectivity in this synthetic approach to molecular constraint with multiple derivatives being formed. Objective: To systematically evaluate the synthesis of covalently crosslinked insulin analogs by asymmetric methods and the biological consequences. Method: We report synthesis of amine crosslinked insulin analogs via a two-step procedure. The stepwise approach was initiated by amide bond formation and followed by second site alkylation to produce site-specific, cross-linked insulin analogs. Results: A set of unique insulin analogs crosslinked at the two of the three native amines were synthesized. They were chemical characterized and assessed by in vitro bioanalysis to result in a significant and reasonably consistent reduction in biological potency. Conclusion: We achieved an unambiguous two-step synthesis of several crosslinked insulin analogs differing in location of the chemical tether. Bioanalysis demonstrated the ability of the molecular constraint to reduce bioactivity. The results set the stage for in vivo assessment of whether such a reduction in potency can be used pharmacologically to establish a constrained hormone upon which reversible tethering might be subsequently introduced.
Keywords: biological potency